A study of the cognitive reading strategies employed by ESL readers - Ibrahim, Noor Aireen; Mat Saman, Nurulsyaida (2010)
Reading is a complex process that requires active participation from readers by which, they need to process and understand information in the texts. Hence, readers can understand the text more effectively if they are able to make use of appropriate reading strategies. The use of effective reading strategies is important as they help readers to minimize time and effort to comprehend a particular text. This research aims to identify and compare the cognitive reading strategies employed by students who have undergone a reading course and students who have not undergone a reading course. The participants chosen for this study were final year students from the Faculty of Education, UTM. All six participants have the same level of proficiency in English. The ‘think-aloud’ technique was used to identify the cognitive reading strategies employed by the participants. A set of questionnaire was distributed to the participants to examine the difference between the participants’ self-reported data and their actual reading strategies. The findings of this study showed that there are differences in the types and frequency of strategies used by the participants both as groups and individually. Future research should examine reading strategies employed by participants with different levels of proficiency.